California Multivariate Ocean Climate Indicator (MOCI) and marine ecosystem dynamics. (January 2017) - García-Reyes, Marisol; Sydeman, William J.
Highlights: MOCI captures ocean & climate processes relevant to California's marine ecosystem. MOCI highlights differences in environmental conditions along the California coast. MOCI is a single index of environmental variability and is easy to use and update. MOCI tracks the effects of ENSO and regional climate events. MOCI relates to ecosystem variability across trophic levels. Abstract: Marine ecosystems are complex adaptive systems with physical and biological processes operating on multiple spatial and temporal scales. Here, we present an operational regional indicator for California's continental shelf system and investigate its skill in predicting a variety of biological responses across trophic levels. This updated Multivariate Ocean Climate Indicator (MOCI) version 2 includes data that are readily available from the Internet so the indicator can be automatically updated and shared regularly. MOCIv.2 is a simplified version of MOCIv.1, but it captures ocean-climate variability similarly. MOCIv.2 illustrates all major ENSO events that occurred over the past 25 years as well as the phasing and magnitude of the most recent North Pacific marine heat wave, dubbed 'The Blob'. It also shows differences in the magnitude and timing of ocean-climate variability in different regions off California. MOCIv.2 has skill in nowcasting marine ecosystem dynamics, from zooplankton to top predators, and therefore may be useful in establishing bio-physical relationships important to ecosystem-based fisheries and wildlife management in California.